Avaliação do nível de contribuição do curso de Administração da UFAM na formação empreendedora - Trindade, Anna Carolina Fróes (Brasil, 2024)
This research aimed to analyze the impact of the UFAM administration course on the entrepreneurial development of students. For this, a quantitative approach was used, whose data were collected through a questionnaire, structured with questions to measure the applicability of acquired knowledge, extracurricular activities and the influence of interactions with professionals in the sector. The results indicate that 51.7% of respondents are influenced by graduation in their desire to undertake. Furthermore, the majority of students recognize the value of practical experiences, such as internships and projects, to apply entrepreneurial knowledge. However, a considerable portion of neutral or negative responses were observed in relation to the University's interaction with the business sector and with practices focused on innovation. These results highlight the importance of improving student engagement strategies with the market and promoting a more effective integration between theory and practice in entrepreneurship within the academic curriculum.